2019
DOI: 10.2147/ndt.s200264
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of key genes, pathways and miRNA/mRNA regulatory networks of CUMS-induced depression in nucleus accumbens by integrated bioinformatics analysis</p>

Abstract: Introduction: Major depressive disorder (MDD) is a recurrent, devastating mental disorder, which affects .350 million people worldwide, and exerts substantial public health and financial costs to society. Thus, there is a significant need to discover innovative therapeutics to treat depression efficiently. Stress-induced dysfunction in the subtype of neuronal cells and the change of synaptic plasticity and structural plasticity of nucleus accumbens (NAc) are implicated in depression symptomology. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 80 publications
(86 reference statements)
2
11
0
Order By: Relevance
“…6. There were evidences that miR-338-3p and pvalb were identi ed to be unnormal expressed in depression, suggesting play a key role pathogenesis of depression [47,48]. MiR-338-3p is a mature miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…6. There were evidences that miR-338-3p and pvalb were identi ed to be unnormal expressed in depression, suggesting play a key role pathogenesis of depression [47,48]. MiR-338-3p is a mature miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for RNA isolation and sequencing was reported in our published study . In brief, after depression‐like behavior tests, mice were anesthetized using isoflurane and rapidly sacrificed by decollation.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 A transcriptome study of the striatum suggested that dysfunction of dopaminergic synapses, GABAergic synapses, and neurotransmitter synthesis is involved in the pathogenesis of chronic unpredictable mild stress (CUMS)-induced depression. 11 It has also been reported that the use of deep brain stimulation in the striatum could reduce 50% of depression symptoms in patients with refractory depression. 12 In addition, depression severity and the antidepressant effects of ketamine have been shown to depend on the structure and function of the striatum.…”
Section: Introductionmentioning
confidence: 99%